Mechanical characterization of Redwood structural timber from Central and Iberian mountains - Fernandez-Golfin, J. I.; Diez, M. R.; Gutierrez, A. (Forest Systems, 1997)
A mechanical characterization of structural timber (150 x 50 x 3.000 mm) of different Spanish provenances of Pinus sylvestris is carried out, giving the characteristic values and strength classes corresponding to the quality classes considered in the UNE 56544 visual grading standard. A criticism of the cited UNE 56544 standard is also included, providing some solutions to the detected problems. A mechanical characterization of timber coming from young small dimater logs is also considered and a discussion about the influence of the intensity of thinnings into the mechanical properties and quality of timber is provided. The feasibility of the use of the UNE 56544 standard is also discussed. A final comparison with the results of other studies on Pinus pinaster and P. radiata is also carried out.